Development of polylactic acid filled with OPEFB fiber, activated carbon and MWCNTs composites used as EMI shielding materials - Lakin, Ibrahim Ismaila (2021)
Microwave absorbers are used in a wide range of applications to eliminate or reduce electromagnetic radiation that could interfere with a system’s operation. There are several materials such as metals, various carbonaceous materials (graphene, carbon nanotubes, graphite powder and carbon fibers), conductive polymers, and their composites which are the ideal candidates for microwave absorbing applications. Conventionally metals have been used for this reason for a long time and act as the most effective microwave absorber, but they have drawback for corrosion, heavy weight and difficult processability. Industries are now concentrating on easy-to-process electrically conducting materials based on conductive polymers, conductive fillers in polymer matrix that not only have semiconductor properties but can also withstand corrosive environments, inexpensive and are light in weight. This thesis presents the development of microwave absorbers using polylactic acid (PLA) and empty fruit bunch (OPEFB) as the host. Two types of absorbers were developed in this work as an alternative for reducing the limitations of metal-based microwave absorbing materials. The first absorber utilized activated carbon (AC) fillers synthesized from OPEFB. The second type used commercial multiwalled carbon nanotubes (MWCNTs) fillers obtained from US Research Nanomaterials, Inc. OPEFB fiber was crushed and sieved to various fiber sizes using laboratory sieve test. The relationship between the different OPEFB fiber sizes and the dielectric properties was then determined. The material composition and structural properties were analyzed using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDX), and fourier transform infrared (FTIR) techniques. The relative complex permittivity of the composites was measured using open-ended coaxial probe technique while the microwave absorption properties were measured with the microstrip. The results showed that relative complex permittivity of the OPEFB fiber increased with reduced fiber size. Additionally, relative complex permittivity of the OPEFB-PLA, OPEFB-PLA-AC, and OPEFB-PLA-MWCNTs increased with filler content and were higher in the OPEFB-PLA-MWCNTs composites. At 10 GHz the dielectric constants of OPEFB-PLA, OPEFB-PLA-AC, and OPEFB-PLA-MWCNTs composites were found to be between 2.98 to 3.40, 3.14 to 3.96 and 3.40 to 4.25 respectively while the loss factor values were from 0.34 to 0.48, 0.41 to 0.52 and 0.51 to 0.64. The measured |S11| and |S21| were used to determine the reflection loss (SER), absorption loss (SEA), and total electromagnetic interference (EMI) shielding effectiveness (SET) of all the composites. The SET values were found to increase with filler loadings and were higher in the OPEFB-PLA-MWCNTs composites than the OPEFB-PLA and OPEFB-PLA-AC composites which is ascribed to the MWCNTs’ high loss factor. At 12 GHz, the range of SET values for OPEFB-PLA-MWCNTs composites was from 20.31 to 25.01 dB while OPEFB-PLA-AC and OPEFB-PLA composites were from 17.45 to 22.25 dB and 10.67 to 12.50 dB respectively, which suggest their usefulness for microwave absorption. AC derived from OPEFB fiber has the potential for use as a filler in polymeric composites and its application can reduce the cost of MWCNTs-based microwave absorbing materials significantly.